2015
DOI: 10.1007/s13204-015-0480-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects on structural, optical, and magnetic properties of pure and Sr-substituted MgFe2O4 nanoparticles at different calcination temperatures

Abstract: In the present work, pure and Sr 2? ions substituted Mg ferrite nanoparticles (NPs) had been prepared by co-precipitation method and their structural, optical, and magnetic properties at different calcination temperatures were studied. On this purpose, thermo gravimetric and differential thermal analysis (TG-DTA), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electron microscopy, UV-Visible diffused reflectance spectroscopy, impedance spectroscopy, and vibrating sample magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…10, the values of the direct optical gap energy of the Fe 3 O 4 nanoparticles are increasing with increasing NaOH concentration. This result is contradictive compared to the result reported by (Dhas, et al, 2015;Heiba, et al, 2015;Loganathan & Kumar, 2016). The indirect optical gap energy also increases with increasing NaOH concentration.…”
Section: Absorbance Spectra and Optical Propertiesmentioning
confidence: 59%
“…10, the values of the direct optical gap energy of the Fe 3 O 4 nanoparticles are increasing with increasing NaOH concentration. This result is contradictive compared to the result reported by (Dhas, et al, 2015;Heiba, et al, 2015;Loganathan & Kumar, 2016). The indirect optical gap energy also increases with increasing NaOH concentration.…”
Section: Absorbance Spectra and Optical Propertiesmentioning
confidence: 59%
“…They observed higher permeabilty and lower magnetization for Nd doped Cu-Zn ferrites as compared to undoped ferrites. Loganathan et al [11] showed that structural, optical, and magnetic properties of Sr-substituted magnesium ferrites strongly depend on calcination temperature. Effect of thermal processing on the tribological of nanocrystalline Ni/TiO 2 coatings have been reported Cooke and Khan.…”
Section: Introductionmentioning
confidence: 99%
“…[14] The lattice constant (a) was decreased with the increase of Al 3+ content, evidenced by the smaller ionic radii of the Al 3+ ions (0.67 Å) than the Cu 2+ ion (0.73 Å) and the Zn 2+ ion (0.83 Å). The observed larger lattice parameter (8.3958 Å) of F 1 may be due to the strong interactions between Al- nanoferrites, which may be due to the magnetic interactions between the particles of ferrites and the limited magnification power of this device [16] or to the magnetic exchange interaction between the nanoparticles [17].…”
Section: Methodsmentioning
confidence: 99%